2014
DOI: 10.1371/journal.pone.0099564
|View full text |Cite
|
Sign up to set email alerts
|

Mapped Clone and Functional Analysis of Leaf-Color Gene Ygl7 in a Rice Hybrid (Oryza sativa L. ssp. indica)

Abstract: Leaf-color is an effective marker to identify the hybridization of rice. Leaf-color related genes function in chloroplast development and the photosynthetic pigment biosynthesis of higher plants. The ygl7 (yellow-green leaf 7) is a mutant with spontaneous yellow-green leaf phenotype across the whole lifespan but with no change to its yield traits. We cloned gene Ygl7 (Os03g59640) which encodes a magnesium-chelatase ChlD protein. Expression of ygl7 turns green-leaves to yellow, whereas RNAi-mediated silence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 45 publications
(47 reference statements)
5
67
0
Order By: Relevance
“…The leaf-color mutation is a good marker for screening the genetic purity of hybrid crops [13]. It has been helpful understanding of chlorophyll anabolism and catabolism, chloroplast development, and photosynthesis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf-color mutation is a good marker for screening the genetic purity of hybrid crops [13]. It has been helpful understanding of chlorophyll anabolism and catabolism, chloroplast development, and photosynthesis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ease of identification, large numbers of leaf-color mutants have been described and characterized in many plant species like Arabidopsis thaliana [3], barley [4], maize [5], rice [6,7,8], soybean [9], sunflower [10], and wheat [11,12]. For example, in rice, more than 200 leaf color mutants have been documented, and 154 responsible genes have been mapped to all 12 chromosomes, of which 53 have been cloned [13]. In soybean, 25 nuclear genes affecting chlorophyll-deficiency have been identified and mapped [9].…”
Section: Introductionmentioning
confidence: 99%
“…Leaf color markers are widely used in maintaining the genetic purity of seeds and as a marker of self-pollination to monitor male sterile lines (Deng et al 2014;Lv et al 2013). The only phenotypic difference between wild type and the wlml1 mutant is a slight difference in plant height and 1000-grain weight (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…More than 180 color mutants were hitherto isolated and characterized in rice, and at least 80 genes (Deng et al 2014;Sun et al 2017). These mutations distributed in 12 chromosomes were cloned, most of which are controlled by a pair of recessive nuclear genes (Qian et al 1996;Wang et al 2008;Xie et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified that most of the leaf color mutants are controlled by a single recessive nuclear gene. For example, many leaf mutants of soybean[33], wheat [36], and rice [37] were all controlled by a single recessive nuclear gene. In addition, there are a few leaf color mutants, in which the traits are controlled by the cytoplasmic gene.…”
Section: Discussionmentioning
confidence: 99%